Implementation of QSPM and Porter’s Generic Strategy to Develop Mechanical Testing Laboratory in Indonesia - Subhan Subhan; Muhamad Elon; Salmen Ginting; Rhian Indradewa; Edi Hamdi (Budapest International Research and Critics University, 2022)
Mechanical testing is needed in almost all industry segments, such as in the automotive, plastics, food, packaging, steel, and medical equipment industries. Some examples of mechanical testing include tensile, compressive, tearing, fracture, puncture, and texture tests on food. This research is a descriptive qualitative type by describing the strategy of PT Premium Testing Lab (PTL) in order to developing new mechanical testing laboratory in Indonesia. PT PTL uses market penetration and differentiation strategies taken from QSPM analysis and Porter’s Generic Strategy for establishing marketing, human capital and operational goals and objectives. The implementation of marketing strategy must also be supported by a good operational plan and strategy in the human capital division. All three must go hand in hand so that the company's goals can be achieved.